Studying working process of shifting the gear in electromechanical mechanism of gearbox control - Mykhalevych Mykola; Silchenko Mykola; Yaryta Alex; Uskov Oleksii (Avtomobilʹnyj Transport (Harʹkov), 2020)
Problem. The article is devoted to improvement of operational parameters of electromechanical automated drive of gear shift of heavy trucks and buses, improvement of the design of the actuator of the gearbox drive gear control, optimizing operation of the algorithm of controlling the automated electromechanical drive of gear shift. Goal. By analyzing information sources, requirements are set for the automated gearbox drive. On the basis of the analysis of existing designs of the gearshift drives in the mechanical transmission boxes, it was concluded that it is expedient to further improve the electromechanical drive of the gear shift with the actuators on the basis of DC motors, as the most current for use in transmission of heavy trucks and buses. Methodology. The main disadvantage of such structures at the moment is seen in the lack of universality of the analogues considered, concerning their use in gearboxes of different production. This, in turn, negatively affects the cost and reliability of the drive. Results. The dynamical processes taking place in the automated switching mechanism are considered, the mathematical model of the electric motor is investigated and the parameters are determined which influence the work process, the types of electric motors used in the technique, the equations used in mathematical modeling are described, the prospects of rational gearbox control are considered. According to the results of the analysis of the obtained results for further improvement, the design of the actuating mechanism of gear shift with two electric motors of direct current of own design is proposed. It is determined that the proposed new interconnections between the structural elements of the gearshift mechanism allow simultaneously obtaining the required speed of the drive, high accuracy of the adjustment, and provide the necessary effort on the synchronizer. A mathematical description of the working process of transmission switching on by automated electromechanical drive of gear shift is executed. Practical value. The mathematical model of the executive mechanism of the electromechanical drive gearbox transmission includes: differential equations that describe the operation of the electric motor of the direct current, as well as the equation of connection.